Analysis of Quantitative Structure-Activity Relationship (QSAR) Of 1,8-Napthalymide-4-Aminoquinoline Derivatives as Antimalarial Compounds - Ika Nur Fitriani; Muhammad Sholahudin; Adi Tiara Zikri (Department of Chemistry Faculty of Science and Technology Walisongo, 2022)
QSAR analysis from derivative compounds of 1,8-naphthalimide-4-aminoquinoline has been carried out with the aim of knowing the quantitative relationship between structure and activity based on the log IC50 value. The modelling was made with two dimensions and geometric optimization is carried out. The AM1 semi-empirical method was used to optimize the geometry of the total energy of 25 compounds. The descriptors in the QSAR calculation were dipole moment, atomic net charge, ELUMO, EHOMO, SAG, SAA, hydration energy, polarizability, and log P. The descriptors were used to find quantitative equations of the relationship between the structure and antimalarial activity.